2005
DOI: 10.1177/0011128704266422
|View full text |Cite
|
Sign up to set email alerts
|

Court Dispositions and Rearrest for Intimate Assault

Abstract: Researchers examining court dispositions and domestic violence recidivism have argued that disposition effectiveness varies by offender characteristics. We extended this research with analyses of 3,662persons arrested for misdemeanor assaults on intimates in Hamilton County, Ohio. The incidence, prevalence, and time to rearrest are examined for arrestees with no filed charges, subsequently dropped charges, court-mandated treatment, probation, jail, and split sentences. No filed charges and probation correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 45 publications
1
35
2
Order By: Relevance
“…In other words, more severe sentences were not uniformly more effective for reducing subsequent violence. Results for jail sentences conflicted with the handful of previous studies that uncovered either similar or higher odds of subsequent violence for individuals who were incarcerated in jail versus other types of sentences (e.g., Davis et al, 1998;Gross et al, 2000;Wooldredge & Thistlethwaite, 2005).…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…In other words, more severe sentences were not uniformly more effective for reducing subsequent violence. Results for jail sentences conflicted with the handful of previous studies that uncovered either similar or higher odds of subsequent violence for individuals who were incarcerated in jail versus other types of sentences (e.g., Davis et al, 1998;Gross et al, 2000;Wooldredge & Thistlethwaite, 2005).…”
Section: Discussioncontrasting
confidence: 91%
“…Gross et al (2000) found no differences in rearrest likelihoods for defendants with jail sentences (suspended or nonsuspended) versus other outcomes including advisement only, private counseling, fines, and probation (see also Davis et al, 1998;Wooldredge & Thistlethwaite, 2005). Finally, as stated previously, published findings related to imprisonment effects on subsequent violence are nonexistent.…”
Section: Relevant Findings From the Literaturementioning
confidence: 62%
See 3 more Smart Citations